Perilaku Hidup Bersih dan Sehat Mahasiswa Fakultas Kedokteran Universitas Tarumanagara - aprilia, riski riski (Jurnal Skala Kesehatan, 2025)
This study aims to determine the description of Clean and Healthy Living Behavior (PHBS) in the 2022 Faculty of Medicine students of Tarumanagara University. The research method used a descriptive approach with a cross-sectional design. Data were collected through an online questionnaire filled out by 167 respondents. The results showed that most students have implemented PHBS well, such as defecation behavior (100%), hand washing (88%), and nail hygiene (89.8%). However, there are still shortcomings in the selection of healthy snacks (47.3% of bad behavior) and the frequency of physical activity (88% less than 5 times/week). Most respondents had also participated in mosquito nets eradication (59.3%) and had high awareness of the dangers of smoking (97% did not smoke). The conclusion of this study shows that although the majority of students have implemented PHBS well, further education is still needed, especially in the aspect of choosing healthy snacks and increasing physical activity.